Marriage Guidance for Prospective Brides from The Perspective of Maslahah Mursalah (Case Study at the Office of Religious Affairs, Wonoasri District, Madiun Regency) - Hariri, Anas Wildan; Syafi'i, Ahmad; Wahyudi, Wahyudi (Civiliza Publishing, 2023)
This study was conducted at the Religious Affairs Office (KUA) of Wonoasri District, Madiun Regency, to evaluate the implementation of premarital marriage guidance for prospective brides and grooms. This study uses a qualitative descriptive approach with a case study method. Primary data were obtained through interviews with presenters and prospective brides and grooms, while secondary data were taken from premarital guidance books and the Wonoasri KUA archives. Marriage guidance is regulated by the Regulation of the Director General of Islamic Community Guidance Number 379 of 2018 and the Decree of the Director General of Islamic Community Guidance Number 172 of 2022, with two implementation methods: indirect guidance (virtual) and face-to-face (regular), lasting for one day with a total of six hours of lessons and a minimum of 10 pairs of prospective brides and grooms. Based on the perspective of maṣlaḥah mursalah, this guidance according to sharia provides understanding and knowledge that is useful as a provision for building a sakinah, mawaddah, and warahmah family.